Superoxide dismutases: Dual roles in controlling ROS damage and regulating ROS signaling - Wang, Ying; Branicky, Robyn; Noë, Alycia; Hekimi, Siegfried (The Journal of cell biology, 2018)
Superoxide dismutases (SODs) are universal enzymes of organisms that live in the presence of oxygen. They catalyze the conversion of superoxide into oxygen and hydrogen peroxide. Superoxide anions are the intended product of dedicated signaling enzymes as well as the byproduct of several metabolic processes including mitochondrial respiration. Through their activity, SOD enzymes control the levels of a variety of reactive oxygen species (ROS) and reactive nitrogen species, thus both limiting the potential toxicity of these molecules and controlling broad aspects of cellular life that are regulated by their signaling functions. All aerobic organisms have multiple SOD proteins targeted to different cellular and subcellular locations, reflecting the slow diffusion and multiple sources of their substrate superoxide. This compartmentalization also points to the need for fine local control of ROS signaling and to the possibility for ROS to signal between compartments. In this review, we discuss studies in model organisms and humans, which reveal the dual roles of SOD enzymes in controlling damage and regulating signaling.